2001
DOI: 10.1021/es000289k
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Imidacloprid in Water by Photo-Fenton and TiO2 Photocatalysis at a Solar Pilot Plant:  A Comparative Study

Abstract: The technical feasibility, mechanisms, and performance of degradation of aqueous imidacloprid have been studied at pilot scale in two well-defined photocatalytic systems of special interest because natural UV light can be used: heterogeneous photocatalysis with titanium dioxide and homogeneous photocatalysis by photo-Fenton. Equivalent pilot-scale and field conditions used for both allowed adequate comparison of the degree of mineralization and toxicity achieved as well as the transformation products generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
1
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(95 citation statements)
references
References 28 publications
3
84
1
7
Order By: Relevance
“…In this study, the degradation of boscalid is likely due to attack of hydroxyl radicals at −H in the three rings (benzene and pyridine rings) leading to four mono and di hydroxylated products and other carboxylic acids (Lagunas-Allué, Martínez-Soria, Sanz-Asensio, Salvador, Ferronato, & Chovelon, 2010). Furthermore, the suggested degradation of imidacloprid is due to the reaction of hydroxyl radicals to form 6-chloronicotinic aldehyde and 6-chloronicotinic acid (Agüera, Almansa, Malato, Maldonado, & Fernández-Alba, 1998;Malato, et al, 2001). …”
Section: Quantification Of Pesticide Degradationmentioning
confidence: 99%
“…In this study, the degradation of boscalid is likely due to attack of hydroxyl radicals at −H in the three rings (benzene and pyridine rings) leading to four mono and di hydroxylated products and other carboxylic acids (Lagunas-Allué, Martínez-Soria, Sanz-Asensio, Salvador, Ferronato, & Chovelon, 2010). Furthermore, the suggested degradation of imidacloprid is due to the reaction of hydroxyl radicals to form 6-chloronicotinic aldehyde and 6-chloronicotinic acid (Agüera, Almansa, Malato, Maldonado, & Fernández-Alba, 1998;Malato, et al, 2001). …”
Section: Quantification Of Pesticide Degradationmentioning
confidence: 99%
“…TiO 2 was chosen as the adsorbent because it is a widely used material in many interface-related studies [21,22] 0021-9797/$ -see front matter Ó 2011 Elsevier Inc. All rights reserved. doi:10.1016/j.jcis.2011.08.040 including the treatment for arsenic pollution [15,23].…”
Section: Introductionmentioning
confidence: 99%
“…Zarei et al [6] showed that the removal efficiency of phenol was 69% after 150 min using photoelectro-Fenton (PEF)/Mn 2+ /TiO 2 nanoparticles for the removal of phenol from aqueous solutions. Nogueira [7] showed that the role of Fe 2+ ions and H 2 O 2 are much more important than that of TiO 2 in the photodegradation of both 4-chloro-phenol (4CP) and dichloro-acetic acid (DCA) under solar irradiation [7].…”
Section: Introductionmentioning
confidence: 99%